Isolamento, purificação e caracterização parcial da estrutura primária de uma ficobiliproteína da alga marinha vermelha Hypnea musciformis (Wulfen) Lamouroux - Nobre, Clareane Avelino Simplicio (2015)
Seaweeds are a rich reserve of substances with biotechnological interest, among these substances it is possible to highlight the phycobiliproteins. These molecules are water-soluble proteins covalently linked to pigments with linear tetrapyrrole structure called bilin, also known as accessory pigment. Thus, the phycobiliproteins form a complex named phycobilisomes, which is a primary structure of light-gathering, showing photosynthetic function. These structures are found in red and Cyanophyceae seaweed. Phycobiliproteins isolated and purified, when structuraly analised, present subunits characterized as alpha, beta and gamma. These proteins can be used as colorants and stabilizers for food, markers of biomolecules, antioxidants and anti-inflammatory agents. In view of the importance of these molecules, this work aimed to isolate, purify and determine the partial primary structure of the beta chain phycobiliprotein present in the red marine algae Hypnea musciformis. The phycobiliprotein (HMp) was isolated by precipitation of proteins with ammonium sulphate and purified by ion-exchange chromatography. The polyacrylamide gel electrophoresis revealed that the HMp has two chains around 20 kDa and 22 kDa. The 22 kDa chain was excised from the gel and digested with proteolytic enzyme trypsin. The peptides from digestion underwent fragmentation in mass spectrometer. The generated fragments were used for sequencing peptides and have identified in databases. Primers were designed to amplify the beta chain gene bhmp from the genomic DNA of the algae. The amplified gene was sequenced and the tool Phred/Phrap/Consed processed the raw data. The final gene sequence has been translated to obtain the partial primary structure of bHMp. The translation resulted in a sequence with 87 amino acid residues and HMp presented identity with various phycoerythrins of red algae.